Hsp72-Mediated Suppression of c-Jun N-Terminal Kinase Is Implicated in Development of Tolerance to Caspase-Independent Cell Death - Gabai, Vladimir L. (American Society for Microbiology, 2000)
Pretreatment with mild heat shock is known to protect cells from severe stress (acquired thermotolerance). Here we addressed the mechanism of this phenomenon by using primary human fibroblasts. Severe heat shock (45°C, 75 min) of the fibroblasts caused cell death displaying morphological characteristics of apoptosis; however, it was caspase independent. This cell death process was accompanied by strong activation of Akt, extracellular signal-regulated kinase 1 (ERK1) and ERK2, p38, and c-Jun N-terminal (JNK) kinases. Suppression of Akt or ERK1 and -2 kinases increased cell thermosensitivity. In contrast, suppression of stress kinase JNK rendered cells thermoresistant. Development of thermotolerance was not associated with Akt or ERK1 and -2 regulation, and inhibition of these kinases did not reduce acquired thermotolerance. On the other hand, acquired tolerance to severe heat shock was associated with downregulation of JNK. Using an antisense-RNA approach, we found that accumulation of the heat shock protein Hsp72 is necessary for JNK downregulation and is critical for thermotolerance. The capability of naive cells to withstand moderate heat treatment also appears to be dependent on the accumulation of Hsp72 induced by this stress. Indeed, exposure to 45°C for 45 min caused only transient JNK activation and was nonlethal, while prevention of Hsp72 accumulation prolonged JNK activation and led to massive cell death. We also found that JNK activation by UV irradiation, interleukin-1, or tumor necrosis factor was suppressed in thermotolerant cells and that Hsp72 accumulation was responsible for this effect. Hsp72-mediated suppression of JNK is therefore critical for acquired thermotolerance and may play a role in tolerance to other stresses.